The 1970s and the Thatcherite Revolution: Crisis of Ideology or Control? - Gino Raymond (Revue Française de Civilisation Britannique)
There is a familiar analysis of the 1970s in Britain, of a country locked in decline, paralysed by recurring confrontations due to the ideological fault-lines between capital and labour, and reliant on a political system undermined by an unspoken consensus shared by the ruling elite that the most that could await a post-war and post-imperial Britain was a ‘soft landing’. In this analysis, the failures of the post-war right and left in Britain provide a platform for a political outsider, Margaret Thatcher, to over-turn the political apple-cart and usher in a new ideological revolution founded on reinvigorated concepts of economic agency and individual choice. This article will argue that the Thatcherite revolution was not so much a crisis for the traditional ideologies of left and right, as an indication of the way politics had moved beyond ideology. Drawing parallels with the apparent rebirth of socialism in France that ran concurrently with the Thatcherite revolution, this article will suggest that the success of Thatcher owes much to the divorce between image and reality and the symbolic power this allows leaders to deploy subsequently. Ultimately, we will argue, Thatcher was willing to steer the transformation of British society in ways that ran contrary to the principles of those assumed to be her intellectual mentors, in order to satisfy her desire for control.